Pengenalan Nilai-Nilai Local Wisdom dalam Pembelajaran Anak Usia Dini Melalui Ruwatan Rambut Gimbal di Taman Kanak-Kanak Pertiwi Sumberwulan Selomerto Wonosobo - Novyana, Anik Klara; Munawaroh, Hidayatu; Sakir, Moh. (Literasi: Jurnal Pendidikan Guru Indonesia, 2024)
This aims to: 1) To find out the introduction of local wisdom values in Pertiwi Sumberwulan Kindergarten. 2) To find out the early childhood learning process through dreadlock rituals at Pertiwi Sumberwulan Kindergarten. 3) To find out the process of introducing local wisdom values in early childhood learning through dreadlock rituals at Pertiwi Sumberwulan Kindergarten. 4) To find out the obstacles or barriers in early childhood learning through dreadlock rituals at Pertiwi Sumberwulan Kindergarten. This type of research uses qualitative research. Data collection techniques using interview methods, observation, documentation after the data is collected and analyzed using data collection, data reduction, data presentation. Based on this research it can be concluded that: 1) The introduction of local wisdom values at Pertiwi Sumberwulan Kindergarten is introduced through market day learning activities, very effective for introducing local wisdom values such as honesty, cooperation and religious values, 2) Early childhood learning through dreadlock rituals at Pertiwi Sumberwulan Kindergarten using video-based learning methods and roleplay is considered effective for stimulating various aspects of child development, 3) The introduction of local wisdom values in AUD learning through dreadlock rituals at Pertiwi Sumberwulan Kindergarten with video-based learning methods can introduce local wisdom values, namely honesty values, art values and historical values, 4) Obstacles or obstacles in introducing the wonosobo dreadlock ritual tradition in early childhood learning to instill local wisdom values in Pertiwi Sumberwulan Kindergarten from several factors that occur such as from children, teachers, and parents.